Diversity and productive potential of timber trees in cocoa agroforestry systems in Alta Verapaz, Guatemala - Villanueva-González, Carlos; Ruiz-Chután, José; Polesny, Zbynek; Kalousova, Marie; Villanueva, Cristóbal; Lojka, Bohdan (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
Timber production in agroforestry systems can improve environmental and economic sustainability, especially for families living in rural areas. Despite its importance in Guatemala, little is known about the potential of wood and its contribution to the sustainability of traditional agroforestry systems. This study aims to analyze the timber resources in cocoa agroforestry systems (CAFS) of different ages, evaluating variables such as floristic composition, species diversity, and the potential to obtain timber from the species present in the evaluated CAFS. Twenty temporary sampling plots of 2,500 m2 were established, and dendrometric variables were measured in all plots. Species occurrence was statistically analyzed by cross-tabulation and Pearson’s Chi-square test (χ2) to determine species’ frequency distribution among the evaluated CAFS ages. Eight hundred twenty-seven trees of 38 species belonging to 19 families were identified. The most represented species in the age range of the evaluated CAFS were Gliricidia sepium (35.07 %), Swietenia macrophylla (19.11 %), and Inga sapindoides (7.62 %). The total shade trees occupied a basal area of 33.29 m2, and a total volume of 352.35 m3 was recorded, of which 148.9 m3 were for commercial use. The most frequent uses of the wood were firewood (38.21 %), thin plank (30.23 %), and poles (22.85 %), while the use of thick plank was the least common (8.71 %). The CAFS in the studied area are characterized by a wide diversity of shade tree species. These results provide a solid basis for promoting sustainable practices that foster the productivity and preservation of these systems, thus contributing to the sustainability and well-being of farmers.